Pengaruh Pelatihan Pasar Modal, Return Investasi, Persepsi Risiko, dan Literasi Keuangan Terhadap Minat Investasi Melalui Aplikasi Online Pada Generasi Z. - Sri Rahayuningsih,; Dyah Rini Prihastuty ,; Kamilatur Ro’fati, (Jurnal Mutiara Ilmu Akuntansi, 2023)
The purpose of this study was to see whether there was any influence from capital market training, investment returns, risk perceptions, and financial literacy on the z generation's investment interest. The method used in this research is a quantitative research method. With a questionnaire data collection tool, with a population of generation z at the University of 17 August 1945 Surabaya Faculty of Economics and Business. The results of this study are that there is an effect of capital market training (X1) on the z generation's investment interest, there is an effect of investment return (X2) on the z generation's investment interest, no effect of risk perception (X3) is found on the z generation's investment interest, and there is an influence of literacy finance (X4) to investment interest in generation z. But if tested Simultaneously all Variables have a Significant effect.